AFRO-BRAZILIAN DANCE AS AN ANTI-RACIST PEDAGOGICAL PRACTICE IN ART CLASSES (Editora Impacto Científico, 2025)
This article analyzes the contributions of Afro-Brazilian dance to Art Education, considering its aesthetic, historical, and pedagogical relevance for the implementation of Law No. 10.639/2003 and for the promotion of anti-racist educational practices. Based on qualitative, bibliographical, and documentary research, the study discusses how Afro-Brazilian dance—grounded in principles of ancestry, corporeality, musicality, and collective creation—constitutes an essential language for recognizing African matrices in Brazil’s cultural formation. The analysis of historical foundations highlights the importance of artists such as Eros Volúsia, Felícitas Barreto, and especially Mercedes Baptista, whose work consolidated Black identity in Brazilian dance and inaugurated a teaching method committed to the appreciation of Afro-diasporic aesthetics. Within the field of Art Education, Afro-Brazilian dance emerges as a pedagogical tool capable of strengthening the self-esteem of Black students, expanding sensitive repertoires, fostering historical awareness, and promoting the confrontation of racism in school environments. Thus, the study demonstrates that teaching Afro-Brazilian dances in Art classes contributes to democratizing access to culture, diversifying aesthetic references, acknowledging ancestral memories, and building educational practices committed to racial justice.DOI: https://doi.org/10.56238/edimpacto2025.090-065